EGFR-TKIs - induced cardiotoxicity in NSCLC: incidence, evaluation, and monitoring - Wang, Yunlong; Qiu, Qinggui; Deng, Xuan; Wan, Mengchao (Frontiers in Oncology, 2024)
The advent of targeted drug therapy has greatly changed the treatment landscape of advanced non-small cell lung cancer(NSCLC), but the cardioxic side effects of targeted drug anti-cancer therapy seriously affect the prognosis of NSCLC, and it has become the second leading cause of death in cancer patients. Therefore, early identification of the cardiotoxic side effects of targeted drugs is crucial for the prevention and treatment of cardiovascular diseases. The cardiotoxic side effects that may be caused by novel targeted drugs epidermal growth factor receptor inhibitors, including thromboembolic events, heart failure, cardiomyopathy, arrhythmia and hypertension, are discussed, and the mechanisms of their respective adverse cardiovascular reactions are summarized, to provide useful recommendations for cardiac management of patients with advanced lung cancer to maximize treatment outcomes for lung cancer survivors. Clinicians need to balance the risk-benefit ratio between targeted therapy for malignant tumors and druginduced cardiotoxicity, and evaluate and monitor TKIs-induced cardiotoxicity through electrocardiogram, cardiac imaging, biomarkers, etc., so as to remove the susceptibility risk factors as soon as possible and provide a reference for the clinical use of such drugs in the treatment of malignant tumors.